Enhancing chicken meat quality with user-friendly decontamination wipes - Talukder, S.; Sen, A.R.; Devadason, I.P.; Biswas, A.K.; Kumar, M.S.; Dhanze, H.; Bhilegaonkar, K.N.; Hung Nguyen-Viet; Grace, Delia; Deka, Ram Pratim (MDPI, 2025)
The unhygienic practices in retail poultry meat shops adversely affect chicken meat quality and shelf life. To address this issue, a meat-surface-decontaminating wipe was developed. Deionized water, jamun leaf (Syzygium cumini) extracts, and other generally recognized as safe ingredients were used to prepare a decontamination solution. A sterile non-woven cloth soaked in the solution was applied over the meat surface as a decontamination wipe. Treated and untreated meat samples were stored at 4 ± 1 °C under aerobic packaging conditions, and various meat quality parameters were evaluated at every 1-day interval until the onset of spoilage. It was observed that the wipe could significantly reduce 2.31 log microbial loads (p = 0.00005, CI-95%, 1.85, 2.77) over the meat surface. With the increasing storage intervals, the meat quality parameters changed significantly (p < 0.05), and the treated chicken samples spoiled on day 6, whereas the control spoiled on day 5. The meat spoilage was confirmed by the evaluation of quality changes in the stored meat. Additionally, the wipe could cause 1.14 (p = 0.00000, CI-95%, 1.01, 1.25) and 1.03 (p = 0.00005, CI-95%, 0.90, 1.16) log reductions of E. coli and S. aureus, respectively. Based on the results, it was concluded that the decontamination wipe could improve the meat quality and shelf life of retail chicken meat without affecting the sensory quality attributes.